US HIGHER ENGINEERING EDUCATION: THE SPOTLIGHT ON CURRENT TRENDS - Pavlenko, Olha (The Modern Higher Education Review, 2019)
US higher engineering institutions have gained the public trust and are holding the leading positions in the world university rankings. Being among one the most popular fields, engineering for many years has received much attention in terms of rethinking the balance of theory and practice, the role of fundamental disciplines alongside with humanities and social sciences, the impact of the technological progress on the scope and learning outcomes of engineering education. The article aims to present research on US higher engineering education tendencies, briefly outline historical prerequisites of major changes in American engineering education, as well as to enhance the understanding of valuable international educational practices. The article discusses advances in engineering curricula design and provides suggestions for improving them in terms of learning outcomes and needs of modern engineers.